2016 23rd International Conference on Pattern Recognition (ICPR) 2016
DOI: 10.1109/icpr.2016.7900130
|View full text |Cite
|
Sign up to set email alerts
|

A 2D shape structure for decomposition and part similarity

Abstract: This paper presents a multilevel analysis of 2D shapes and uses it to find similarities between the different parts of a shape. Such an analysis is important for many applications such as shape comparison, editing, and compression. Our robust and stable method decomposes a shape into parts, determines a parts hierarchy, and measures similarity between parts based on a salience measure on the medial axis, the Weighted Extended Distance Function, providing a multi-resolution partition of the shape that is stable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…We then order the reduced set of branches according to branch importance. For both steps, we use a salience measure, the Weighted Extended Distance Function (WEDF) function on the skeleton [20], to determine the relative importance of branches. The WEDF function has been shown to measure relative importance of shape parts in a way that matches human perception [8].…”
Section: Parametric Skeletonsmentioning
confidence: 99%
“…We then order the reduced set of branches according to branch importance. For both steps, we use a salience measure, the Weighted Extended Distance Function (WEDF) function on the skeleton [20], to determine the relative importance of branches. The WEDF function has been shown to measure relative importance of shape parts in a way that matches human perception [8].…”
Section: Parametric Skeletonsmentioning
confidence: 99%
“…While most of the 3D methods described above do not make use of skeletons, in part because of their perceived instability and difficult to compute, recent methods for 2D shape analysis, decomposition and clustering [5,6,31] successfully exploit the geometry of the Blum medial axis for various shape tasks. These methods have shown that the use of the skeletons can be complemented with properly chosen functions that provide robustness and stability.…”
Section: Preliminariesmentioning
confidence: 99%
“…Below, we introduce such a measure, called Weighted Extended Distance Function (WEDF), which is defined on a curve skeleton centered within a 3D shape. WEDF has been introduced recently for 2D shape contours [5] and successfully used for defining a salience measure and decomposition of 2D curves [6]. Generalizing to the 3D setting takes two steps: first defining WEDF on a 3D skeleton and deducing a partition, second, mapping the measure on the surface mesh.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this challenge, a pre-segmented image dataset with the corresponding skeleton representations in three tracks is provided [25]. The first track has posed the challenge of extracting the skeleton pixels from the given pre-segmented images [25] [16] [19] [24]. We have approached this challenge as an edge detection problem and introduced a version of HED architecture in the decoder part of our proposed architecture.…”
Section: Introductionmentioning
confidence: 99%